Hubungan Antara Lingkungan Kerja Dengan Kepuasan Kerja Pada Pegawai Badan Narkotika Nasional Provinsi Sumatera Utara - Daulay, Afifah Amalia; Lubis, Doli Maulana Gama Samudera (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2024)
This research aims to determine the relationship between the work environment and employee job satisfaction at the Narcotics Agency of North Sumatra Province. The total sample in this study was 73 employees who were registered as permanent employees. This research uses quantitative methods. The subjects in this study were employees of the National Narcotics Agency of North Sumatra Province. The sampling technique in this study used a total sampling technique. Data collection was carried out using a Likert scale model for the work environment scale and job satisfaction scale. Based on the results of research conducted, it shows that a conducive work environment at the North Sumatra Province BNN has a positive effect on employee satisfaction and performance. Physical and non-physical factors such as room conditions, relationships between employees, management, and organizational culture are very important. Although there are challenges, wise management and effective communication can overcome them. Statistical tests show that the work environment contributes 18% to job satisfaction. Therefore, leaders must improve working conditions, communication and organizational culture.